2015
DOI: 10.1021/acs.nanolett.5b00396
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Configurable Graphene Field-Effect Transistors with a Graded-Potential Gate

Abstract: A device architecture for electrically configurable graphene field-effect transistor (GFET) using a graded-potential gate is present. The gating scheme enables a linearly varying electric field that modulates the electronic structure of graphene and causes a continuous shift of the Dirac points along the channel of GFET. This spatially varying electrostatic modulation produces a pseudobandgap observed as a suppressed conductance of graphene within a controllable energy range. By tuning the electrical gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
(60 reference statements)
0
23
0
1
Order By: Relevance
“…[2][3][4][5] Recently, the rising stars of 2D materials have presented excellent electronic and optoelectronic properties [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] including ultrafast carrier dynamics, layer-dependent energy bandgap, tunable optical properties, low power dissipation, high mobility, transparency, etc. [2][3][4][5] Recently, the rising stars of 2D materials have presented excellent electronic and optoelectronic properties [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] including ultrafast carrier dynamics, layer-dependent energy bandgap, tunable optical properties, low power dissipation, high mobility, transparency, etc.…”
mentioning
confidence: 99%
“…[2][3][4][5] Recently, the rising stars of 2D materials have presented excellent electronic and optoelectronic properties [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] including ultrafast carrier dynamics, layer-dependent energy bandgap, tunable optical properties, low power dissipation, high mobility, transparency, etc. [2][3][4][5] Recently, the rising stars of 2D materials have presented excellent electronic and optoelectronic properties [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] including ultrafast carrier dynamics, layer-dependent energy bandgap, tunable optical properties, low power dissipation, high mobility, transparency, etc.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13] Most notably, the highest quality graphene-hBN vdW structures, with ballistic electron propagation at the micron length-scale, enable one to exploit the unique crystalline structure and conductive properties of graphene [14][15][16] in order to construct transistors featuring highly controllable I-V characteristics. 12,17,18 In particular, the work of Mishchenko et al 12 demonstrated the possibility of producing vertical-tunnelling fieldeffect transistors featuring a pair of graphene electrodes with well aligned crystallographic axes (misaligned by h % 1 ). Such devices exhibit strong resonant peaks in their current characteristics, which precipitate the onset of negative differential conductance (NDC) which has been used to generate radio frequency oscillations when connected to an LC circuit.…”
mentioning
confidence: 99%
“…Another interesting observation is that changing the S/D doping concentration modulates minimum conduction point known as the Dirac point; the point at which I ds is minimum. Earlier studies show that the Dirac point can be changed by varying the drain to source voltage [27] or by some other variations in the GNRFET [16, 27–30]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Much research has been done on GNRFET with respect to channel doping [15, 16], gate oxide [17], gate material [18], dimensional scaling [19] and defects [20]. However, there is much more scope of research with respect to S/D doping concentration.…”
Section: Introductionmentioning
confidence: 99%